2022
DOI: 10.1111/ahe.12880
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of the Egyptian Ossimi sheep tongue: New scanning electron microscopic insights into its papillary system adaptations to Egyptian ecological conditions

Abstract: The current study aims to illustrate the gross and scanning electron microscopic characterizations and ultrastructural adaptation of the lingual papillary system of Egyptian Ossimi sheep to Egyptian ecological conditions. The tongue had three regions: the apex (with a slightly bifurcated tip), the body (subdivided into rostral and caudal parts) and the root (subdivided into rostral papillary and caudal non‐papillary parts). Torus linguae had two parts: the triangular rostral part (the caudal part of the body) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 43 publications
7
11
0
Order By: Relevance
“…These morphological adaptations to the Nubian goats grazing habits are compatible with the main characteristics of several taxonomic groups. Our results revealed that the ventral surface of the apex was classified into the smaller rostral papillary region on the tip and the larger non‐papillary region by the U‐line of the filiform papillae, similar to that reported in Egyptian Ossimi sheep (Abumandour et al, 2022b). Meanwhile, similar results were reported in the Egyptian water buffalo, but the projected U‐line separating the papillary and non‐papillary regions consisted of projected fungiform papillae (El‐Bakary & Abumandour, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These morphological adaptations to the Nubian goats grazing habits are compatible with the main characteristics of several taxonomic groups. Our results revealed that the ventral surface of the apex was classified into the smaller rostral papillary region on the tip and the larger non‐papillary region by the U‐line of the filiform papillae, similar to that reported in Egyptian Ossimi sheep (Abumandour et al, 2022b). Meanwhile, similar results were reported in the Egyptian water buffalo, but the projected U‐line separating the papillary and non‐papillary regions consisted of projected fungiform papillae (El‐Bakary & Abumandour, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Considering that the tongue of ruminants is an organ well‐matched to the processes of chewing and ruminating food, morphology with lingual prominence and distribution of lingual papillae appear to be traditional characteristics in both primary feeding groups, namely grazers and browsers (Shipley, 1999). Previously published data described variability of ruminant anatomical lingual lineaments as an evolution key for understanding feeding strategies based on the type of available food particles, ecological conditions and the feeding mechanism appropriate to each species (Abumandour et al, 2022b; El‐Bakary & Abumandour, 2017; Kurtul & Atalgin, 2008). Feeding behaviour observations in Nubian goats show that they feed primarily on dried grasses and herbs and may browse on the leaves of trees and bushes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations